2019
DOI: 10.3390/medicina55060228
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Atrial Electromechanical Delay in Children with Obesity

Abstract: Background and Objective: Childhood obesity is one of the worldwide health problems with an increasing prevalence and accompanied by severe morbidity and mortality. It is a serious predisposing risk factor especially for the development of cardiovascular diseases and arrhythmias. Electromechanical delay (EMD) is known to be a predictor for the development of atrial fibrillation (AF). Our study aims to investigate whether EMD, which is a predictor of AF, prolongs in obese children or not. Material and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 39 publications
(48 reference statements)
1
11
0
2
Order By: Relevance
“…It has been demonstrated that atrial electromechanical delay predicts arrhythmias in studies conducted with adults and children. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Although its mechanism has not been completely understood in obesity, pro-inflammatory cytokines like interleukin-1, interleukin-6 and tumour necrosis factor-α which are secreted from visceral and epicardial adipose tissue may cause atrial electromechanical delay by causing inflammation in atrial tissue. 29 A decrease in visceral and epicardial adipose tissue may also cause a decrease in electromechanical delay by further reducing existing inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that atrial electromechanical delay predicts arrhythmias in studies conducted with adults and children. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Although its mechanism has not been completely understood in obesity, pro-inflammatory cytokines like interleukin-1, interleukin-6 and tumour necrosis factor-α which are secreted from visceral and epicardial adipose tissue may cause atrial electromechanical delay by causing inflammation in atrial tissue. 29 A decrease in visceral and epicardial adipose tissue may also cause a decrease in electromechanical delay by further reducing existing inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] It has been known that electromechanical delay predicts atrial fibrillation and it has been demonstrated that obese children have electromechanical delay. 12 However, the effects of metformin on electromechanical delay in obese children with insulin resistance have not been known.…”
mentioning
confidence: 99%
“…Electromechanical conduction prolongation has been shown to be prone to atrial fibrillation. 31 IR, which is frequently associated with obesity, has an effect on atrial functions due to existing subclinical inflammation. In our study, both intra-and inter-atrial conduction time was found to be higher in obese children with insulin resistance, according to the literature, compared to the non-IR group.…”
Section: Discussionmentioning
confidence: 99%
“…For all measurements, the average of at least three cardiac cycles was evaluated. For the conventional Doppler echocardiographic examinations and M-mode measurements, the European Society of Echocardiography guideline criteria were used [17].…”
Section: Methodsmentioning
confidence: 99%